2022
DOI: 10.1021/acssuschemeng.2c03346
|View full text |Cite
|
Sign up to set email alerts
|

Spent Li-Ion Battery Electrode Material with Lithium Nickel Manganese Cobalt Oxide as a Reusable Catalyst for Oxidation of Biofurans

Abstract: The wide use of Li-ion batteries in energy storage has resulted in a new waste product stream rich in valuable metals Mn, Ni, and Co with well-known catalytic activities. In this work, a spent Li-ion battery electrode material with lithium nickel manganese cobalt oxide is shown as an excellent reusable catalyst for oxidation of biomass-derived furan aldehydes and alcohols to their value-added oxidation products with applications in the sustainable polymer industry. A mechanically separated, combined cathode an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In this context, Amarasekara et al reported innovative approaches to enhance the value of biomass-derived compounds through conversion by recycled catalysts from spent LIBs [30][31][32]. The recycling of LIBs for reuse as catalysts involved a discharging and mechanical dismantling process (Figure 2a).…”
Section: Catalyst From Spent Lithium-ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Amarasekara et al reported innovative approaches to enhance the value of biomass-derived compounds through conversion by recycled catalysts from spent LIBs [30][31][32]. The recycling of LIBs for reuse as catalysts involved a discharging and mechanical dismantling process (Figure 2a).…”
Section: Catalyst From Spent Lithium-ion Batteriesmentioning
confidence: 99%
“…Interfering organic residues, e.g., binders, were removed by pyrolyzing the cathode and anode black material at 600 • C. After grinding and sieving, the resulting powder of LiNi x Mn y Co z O 2 /C was used as a catalyst (Figure 2b). The authors demonstrated the practicability of this catalyst for the transformation of different biomass-derived substrates, namely the oxidation of cellulose-derived furans to their corresponding carboxylic acids [30], the oxidation of D-glucose to glycolic acid [31], and the decarboxylative dimerization of levulinic acid [32]. For example, the oxidation of furans, including furan-2-aldehyde, 5-hydroxymethyl furfural, and 5,5 ′ -[oxybis(methylene)]bis [2-furaldehyde], achieved moderate-to-high yields ranging from 82% to 97% depending on the substrate used.…”
Section: Catalyst From Spent Lithium-ion Batteriesmentioning
confidence: 99%
“…We have been studying the catalytic activities of the lithium nickel manganese cobalt oxide with the general formula Li a Ni b Mn c Co d O e derived from spent Li-ion battery waste for oxidation of sugars as well as biomass-derived furans for producing value-added products such as glycolic acid in recent years [33,34]. In addition, we have reported the use of lithium nickel manganese cobalt oxide as a catalyst for decarboxylative dimerization of levulinic acid in upgrading this biomass-derived carboxylic acid [35].…”
Section: Introductionmentioning
confidence: 99%